Parents’/Carers’ Expectations and Perceptions of Structured Aquatic Taught Baby Programmes: An Online Survey - Debbie, M Smith; Anja, Wittkowski (Journal of Women's Reproductive Health, 2016)
Although structured taught aquatic baby programmes (STABPs) are one of the earliest forms of physical activity, the possible impacts of structured taught aquatic baby programmes are unknown. This study aims to understand the perceived impact that attending STABPs has on parents/carers, their baby/child and their family. An online survey was completed by 2854 parents/carers. It was advertised via numerous online advertisements. Of the respondents, 89% had attended STABPs. ‘Attendees’ were significantly older and were less likely to live in a more deprived area compared to ‘non-attendees’. STABPs are perceived to be beneficial in terms of water safety, confidence, benefits to parent-child relationships and interaction with other children but cost affects attendance. The evidence-base regarding the benefits of STABPs should be established to further understand their impact on parents/carers and babies. Further research should focus on understanding barriers to attendance and ways to facilitate attendance. The need to understand the ‘key ingredients’ of structured taught aquatic baby programmes was highlighted.
Keywords: Structured taught aquatic baby programmes; physical activity; baby wellbeing; parental wellbeing; water confidence and mother-baby attachment.Running title: